IMPLEMENTASI STRATEGI EMPLOYER BRANDING DALAM MENARIK TALENTA BERKUALITAS PADA PERGURUAN TINGGI TERKEMUKA - Giarta, Jemicha Endra; Donald Crestofel Lantu (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2025)
Employer branding is a strategic approach to attracting and retaining top talent, particularly from leading universities. This study aims to analyze the implementation of employer branding strategies in attracting high-quality candidates, using a mixed-method approach that combines a survey of 133 students from three top Indonesian universities and interviews with company alumni. The results show that development value, social value, and application value are the most appreciated dimensions among students. However, there is a noticeable gap between the employer value proposition (EVP) communicated by the company and the candidates’ perceptions. This misalignment may reduce the effectiveness of branding strategies if not addressed. The study recommends aligning the EVP with internal realities, engaging alumni as branding ambassadors, and designing transparent career development paths. These findings are expected to serve as a reference for companies in formulating talent acquisition strategies that align with the expectations of the younger generation.